Determining Bedrock Quality by Geoelectric Method: A Soil Investigation Study in Moramo District, South Konawe Regency, Indonesia - Tachrir Tachrir (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
In comparison to the findings of deep drilling, this study tries to describe the depth of bedrock and soil layers. Wawatu Village, North Moramo District, South Konawe Regency, Southeast Sulawesi Province, Indonesia, served as the location for data collection. Kendari City is 30 kilometers away from the settlement. The community has three borders: the Sea to the east, Wawatu community to the south, and Tanjung Tiram Village to the north. Additionally, it shares a boundary with Abeli Village to the west. The settlement of Wawatu is located at 40 3' 35